THERAPEUTIC PROPERTIES OF CAPSAICIN: A MEDICINALLY IMPORTANT BIO-ACTIVE CONSTITUENT OF CHILLI PEPPER - SINGH, SANGRAM; UDDIN, MOIN; KHAN, M. MASROOR A.; SINGH, SARIKA; CHISHTI, AMAN SOBIA; BHAT, UROOJ HASSAN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Plants are the source of numerous pharmaceutically important compounds that have been employed to cure various human ailments since ancient times. With the assistance of modern chemistry and materials science, such pharmaceutically important compounds have been identified and isolated to produce new drugs. Alkaloids are one of the most significant classes of naturally occurring secondary-metabolites, which are synthesized and widely distributed in various parts of plants. They regulate various metabolic activities and induce physiological responses in the human body. Capsaicin is a naturally occurring alkaloid found in many species of peppers and is attributed to their spicy nature and pungent flavor. This alkaloid is a member of the Capsaicinoids group, which includes capsaicin, homocapsaicin, homodihydrocapsaicin, dihydrocapsaicin, and nordihydrocapsaicin. Capsaicin has a wide range of therapeutic potential against various human ailments. In this article, we provide a comprehensive overview of the capsaicin molecule as well as an examination of its medicinal properties in a variety of human disorders, including pain, various types of cancer, ulcers, diabetes, obesity, inflammation, cardiovascular diseases, and neurodegenerative diseases.